Validation of the prognostic Heidelberg re-irradiation score in an independent mono-institutional patient cohort - Niyazi, Karim-Maximilian; Flieger, Maya; Ganswindt, Ute; Combs, Stephanie; Belka, Claus (Radiation oncology, 2014)
Re-irradiation has been shown to be a valid option with proven efficacy for recurrent high-grade glioma patients. Overall, up to now it is unclear which patients might be optimal candidates for a second course of irradiation. A recently reported prognostic score developed by Combs et al. may guide treatment decisions and thus, our mono-institutional cohort served as validation set to test its relevance for clinical practice.